Uma história socioeconômica da Igreja: ineclesiamentos, reformas e paroquializações na Itália, a partir do caso de Orvieto (1029-1157) - Felipe Augusto Ribeiro (2019)
This work deals with the history of italian cities in the eleventh and twelfth centuries. From a case study on Orvieto, it analyzes the processes of constitution and consolidation of a city, taken as a specific church: the establishment of a see, the affirmation of diocesan jurisdiction, the accumulation of ecclesial patrimony, the socioeconomic organization around places of worship (inneclesiamento). Starting from these reflections, the thesis problematizes the possible relations between the reformist initiatives of ecclesial community life, proposed during the eleventh century, and the establishment of communal regimes, throughout the twelfth century. To this end, the main sources of the research were the charthers gathered in the Codice diplomatico della città dOrvieto, compared with secondary sources such as chronicles, hagiographies and annals. Analyzing this documentation as a product of social networks, the research attempts to highlight the character initially decentralized of the Orvietan Bishopric, the divisions by which the ecclesial institutions of the city passed, the fluid and multifaceted relations that they nurtured with the rural socioeconomic poles and the subsequent process of centralization of these various centers of power around the local see and canonical chapter. This thesis concludes that Orvietos region went by a urbanocentric development process over the aforementioned centuries until the city made the whole adjacent field turn in its orbit. In order for this to happen, the see and the canonical chapter were converted by the reforms in independent lordhips, able to obtain the submission of the other landlords scattered throughout the diocese.